THE EFFECT OF BRAND IMAGE, PRODUCT KNOWLEDGE AND PRODUCT QUALITY ON PURCHASE INTENTION OF NOTEBOOK WITH DISCOUNT PRICE AS MODERATING VARIABLE - Erida Erida; Ari Sonang Rangkuti (Management Department, Faculty of Economics and Business, Universitas Jambi, 2017)
The purpose of this study are: (1) explaining the effect of brand image, product knowledge and product quality toward purchase intention of Asus Notebook, and (2) explaining the discount price capability on moderating the effect of brand image, product knowledge and product quality toward purchase intention. Research is that through survey, where data collection is: obeservation, interview, and questioning delivery to 99 respondents. Research result shows that brand image, product knowledge and product quality simultaneously effected significantly on purchase intention. Futhermore, partially brand image and product quality found effected significantly on purchase intention. However, product knowledge has not significant effect on purchase intention. Meanwhile, discount price be able to strengthen the effect of brand image, product knowledge and product quality on purchase intention, with discount price as pure moderator variable (product knowledge) and potential moderator variable (brand image and quality product). This shows that the company’s marketing efforts through promotion and it’s product effectively to deliver value to be given to consumers. Hence, that good maintaining on brand image, product quality and discount price should be positioned as marketer strategy to stimulate consumers purchase intention. Keywords : Brand Image, Product Knowledge, Product Quality, Discount Price, Purchase Intention